An Open-label Clinical Study of Chronic L-theanine Supplementation in Patients with Major Depressive Disorder (P12-007-19). (13th June 2019) - Hidese, Shinsuke; Ota, Miho; Ozawa, Hayato; Okubo, Tsutomu; Kunugi, Hiroshi
Abstract: Objectives: The present study is designed to investigate the effectiveness of L-theanine (Suntheanine®) among patients with major depression disorder (MDD). Methods: Twenty patients were recruited with moderate MDD (4 males; mean age: 41.0 ± 14.1 years, and 16 females; 42.9 ± 12.0 years) for this open-label clinical study. Participants were supplemented with L-theanine (250 mg/day) along with their current medication for 8 consecutive weeks. The cognitive functions and related symptoms were evaluated at baseline, 4 weeks, and 8 weeks after L-theanine supplementation using advanced version (21-items) of the Hamilton Depression Rating Scale (HAMD-21), Pittsburgh Sleep Quality Index (PSQI), State-Trait Anxiety Inventory (STAI), Brief Assessment of Cognition in Schizophrenia (BACS), including the Stroop test. Results: L-theanine supplementation effectively lowered the HAMD-21 score ( P  = 0.007), and reduction was also observed in unremitted patients (HAMD-21 > 7; P  = 0.004) at baseline. STAI test results indicated a significant decrease in Anxiety-trait scores ( P  = 0.012) after L-theanine supplementation. PSQI scores also decreased in the unremitted patients at baseline after L-theanine intake ( P  = 0.030). Concerning to the cognitive functions, response latency ( P  = 0.001) and error rate ( P  = 0.036) were lowered in the Stroop test, while executive function ( P  = 0.016) and verbal memory ( P  = 0.005) were significantly enhanced in the BACS test after L-theanine supplementation. Conclusions: This study demonstrates that chronic L-theanine supplementation (8 weeks) is quite safe and features with diverse beneficial effects on the improvement of depressive symptoms, sleep disturbance, anxiety, and cognitive impairment functions in patients with MDD. Funding Sources: This study was supported by an unrestricted research grant provided by the Taiyo Kagaku Co. Ltd.